Fauna of parasite of cyprinids and percoids in the reservoirs of the Moscow Canal - N. N. Romanova; N. A. Golovina; A. A. Vishtorskaya; P. P. Golovin (Российский паразитологический журнал, 2021)
The purpose of the research is determination of the species composition of parasites of cyprinid and percoid fish in the reservoirs of the Moscow Canal.Materials and methods. In 2019–2020, parasitological material was collected in the spring, summer and autumn from percoid (the pike perch and European perch) and cyprinid fish (the bream, silver bream, roach, rudd and sabrefish) aged 2 to 7 years from the reservoirs of the Moscow Canal (Ikshinsky, Pestovsky, Pyalovsky and Klyazminsky Reservoirs) by the methods generally accepted in ichthyo-parasitology. To quantify the fish infection rate, we used the incidence or prevalence of infection, the intensity of infection, and the mean amplitude of the intensity of infection. We used Kabiosh index (K) to assess the species diversity of parasites. Results and discussion. The parasitological analysis results of percoids and cyprinids from the reservoirs of the Moscow Canal are presented. 34 parasite species were found in fish, which belong to nine taxonomic groups: Microsporidia, Myxosporea, Monogenea, Cestoda, Trematoda, Nematoda, Acanthocephala, Hirudinea, Crustacea. The largest number of species belongs to trematodes, the rest, taxa (mixo- and microsporidia, cestodes, nematodes, acanthocephalans, leeches and parasitic crustaceans), are represented singly. We calculated the species diversity ratio (R) of fish parasites in the reservoirs, which ranged from 0.335 to 0.575, which indicates the fauna similarity from 50 to 75%. The greatest similarity in the parasite fauna was found in the roach (R = 0.168–0.447), the least in the European perch (R = 0.447–1.0). We have identified the dominant species that are found in more than 20% of the studied fish and determine the “core” of the parasitic fauna, which included 4 parasite species of epizootic and 1 parasite species of epidemiological significance.